DESKRIPSI PEMAHAMAN KONSEP SISWA PADA MATERI PERUBAHAN KIMIA DAN FISIKA DI KELAS VII SMP - Junarti, Junarti; Enawaty, Eny; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of the research was to describe the student's understanding concept in chemical and physic changes of grade VII SMP Negeri 1 Sungai Raya. The form of the research was descriptive and the method of this research was case study that involved 36 students. The instrument used were a test of learning outcome in the form of essay and interview guide. The result showed most students had an understanding of the concept in; (1) the explain difference of chemical and physic changes of a substance was 41.3% with category: fairly; (2) analyzing chemical change from a sample experiment in a laboratory was 59.7% with category: fairly; (3) analyzing chemical change in daily life was 41.4% with category: fairly; (4) analyzing physic change in daily life was 48.6% with category: fairly; (5) mentions three change of the substance of physic change was 76.8% with category: good; and (6) the determine physic change of the experimental result was 27.8% with category: less. The student’s understanding concept in average was 49.2 with category: fairly.Keywords: Concept, Chemical Change, Physic Change.